Differences In Effectiveness Between Progressive Muscle Relaxation Therapy And Slow Deep Breathing Therapy On Elderly Sleep Quality - Wajihahni Rodiyah; Bintang Tatius; Novita Sari Dewi (RSUP Dr. Kariadi, 2024)
Background Every individual has a lifetime, starting from the womb, born into the world, to becoming elderly. Aging is a process of gradual loss of tissue's ability to repair itself, maintain its normal structure and function so that it cannot defend the tissue from injury (including infection), and repair the damage that occurs. In the elderly, there are various kinds of health problems such as sleep disorders. Sleep disorder or insomnia is a person's inability to sleep. Poor sleep quality can be improved in various ways such as relaxation techniques. Aim To compare the effectiveness of Jacobson's Progressive Muscle Relaxation (JPMR) and Slow Deep Breathing Therapy in improving sleep quality in the elderly. Method This type of research was a quantitative quasi-experiment with pretest and post-test methods (one group pre-test and post-test design). Respondents involved 49 people while research data were processed with the Mann-Whitney and Wilcoxon tests. The Sleep Quality Questionnaire used the PSQI questionnaire. Result The Wilcoxon test with an alternative to the Mann-Whitney test showed no significant difference in effectiveness between the two therapies with p-value = 0.274. Conclusion Both therapies had almost the same level of effectiveness; there was no significant difference between the two, so progressive muscle relaxation therapy and Slow Deep Breathing were equally effective in treating anxiety and improving sleep quality.